IDS Announces Stock Repurchase Program (PR Newswire, 1999)
HOUSTON, June 30 /PRNewswire/ -- Industrial Data Systems Corporation (Amex: IDS) ("the Company") today announced that its board of directors has authorized the repurchase of up to 400,000 shares of its outstanding common stock. The shares will be purchased from time to time in the open market, subject to market conditions and Securities and Exchange guidelines.